2007
DOI: 10.1093/brain/awm175
|View full text |Cite
|
Sign up to set email alerts
|

Developmental lineage of cell types in cortical dysplasia with balloon cells

Abstract: Focal cortical dysplasia type IIB with Ballon cells is a developmental malformation of the cerebral cortex highly associated with epilepsy. As a strategy to define the embryonic origin and neurochemical phenotype of cells in this disease, we probed specimens (n = 10) resected during epilepsy surgery with a panel of 13 antibodies recognizing proteins associated with (i) specific progenitor cell types including brain lipid binding protein (BLBP), collapsin response mediator protein 4 (CRMP4), Dlx1, Dlx2, GFAPdel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
80
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(95 citation statements)
references
References 54 publications
12
80
0
3
Order By: Relevance
“…Loss of Tsc1 or Pten in hippocampal neurons in vitro lead to an increase in the ratio of excitation to inhibition at the network level, although through divergent mechanisms (Weston et al 2014). These findings provide experimental support to observations in human tuber and FCDIIB specimens, which show reduced numbers of GABAergic inhibitory interneurons (White et al 2001;Calcagnotto et al 2005;Lamparello et al 2007).…”
Section: Mtor Malformations and Epileptogenesis: Distinct Mechanistsupporting
confidence: 77%
“…Loss of Tsc1 or Pten in hippocampal neurons in vitro lead to an increase in the ratio of excitation to inhibition at the network level, although through divergent mechanisms (Weston et al 2014). These findings provide experimental support to observations in human tuber and FCDIIB specimens, which show reduced numbers of GABAergic inhibitory interneurons (White et al 2001;Calcagnotto et al 2005;Lamparello et al 2007).…”
Section: Mtor Malformations and Epileptogenesis: Distinct Mechanistsupporting
confidence: 77%
“…In our previous studies, we showed that GFAPd is expressed in balloon cells in focal cortical dysplasia and hemimegalencephaly, and in giant cells in tuberous sclerosis complex (Lamparello et al, 2007;Martinian et al, 2009). Because at that time, GFAPd was only described in SVZ astrocytes (Roelofs et al, 2005), an area in which neural progenitors are located, we put forward the idea that the GFAPd subpopulation of balloon cells retains a progenitor phenotype or represents an influx of newly generated astrocytes from the SVZ.…”
Section: Research Articlementioning
confidence: 90%
“…Evaluation of doublecortin expression patterns in FCD I, compared with normal developing and mature cortex, indicates delayed or abnormal cortical maturation rather than ongoing cytogenesis [138]. Moreover, the application of different cortical layer markers in the evaluation of FCD I and FCD II [109,139] demonstrates that FCD I cases in younger patients were characterized by abnormal expression in layer II for Tbr1 and Otx1, whereas FCDII showed distinct labeling of balloon cells (Pax6, ER81, and Otx1) and dysmorphic neurones (Tbr 1, N200, and Map1b), supporting origins from radial glia (as previously shown [139]) and intermediate progenitor cells, respectively [109].…”
Section: Pathogenesis and Molecular Geneticsmentioning
confidence: 99%